Strategi Pengembangan Obyek Wisata Alam Curug Bayan dalam Meningkatkan Perekonomian Desa Ketenger Kecamatan Baturraden Kabupaten Banyumas - Pratama, Anggi Galih; Hanafi, Fahrudin (Edu Geography, 2021)
With the existence of tourism, a country especially the local government of tourist attraction including managers and tourism economic activists will get income from tourism attraction. Desa Ketenger is famous for the natural beauty, there are nine waterfalls (curug) that never dry out even in the dry season. Desa Ketenger is a village that has a tourist spot namely Curug Bayan which is the location that will be the object of research. The potential of the Curug Bayan tourism attraction needs to be balanced with comprehensive management. This research aims to know the internal and external factors and development strategies of the Curug Bayan Tourism Attraction, and how they contribute to the village economy. This research is quantitative tend. The responder of this research are tourists and the people of Desa Ketenger, especially those who carry out economic activities in the area of Curug Bayan Tourism Attraction. The sampling used a proportionate random sampling technique and to determined the number of samples the researcher used the Slovin formula with an error rate of 15% so that based on the calculation, we get 42 respondents for tourists and 44 respondents for villagers. The data collection techniques were questionnaire, observation, and documentation. This research used a SWOT analysis and descriptive analysis. The results showed that in the Matrix Grand Strategy, development respondents were in quadrant 1 or growth strategy, that is to make optimal use of the strengths and opportunities they have. The contribution of the Curug Bayan Tourism Attraction to the village government is 2% annually. Desa Ketenger merupakan desa yang mempunyai tempat wisata berupa Curug Bayan yang merupakan lokasi yang akan menjadi obyek penelitian Potensi yang dimiliki obyek wisata Curug Bayan perlu ada pengembangan yang diimbangi dengan manajemen secara komprehensif. Tujuan dalam penelitian ini adalah mengetahui faktor internal dan eksternal dan strategi pengembangan Obyek Wisata Curug bayan, dan bagaimana kontribusinya dalam perekonomian desa. Penelitian ini bersifat kuantitatif. Populasi penelitian ini adalah wisatawan dan masyarakat desa Ketenger khususnya yang melakukan aktivitas ekonomi di area Obyek Wisata Curug Bayan. Pengambilan sampel menggunakan teknik proportionate random sampling dan untuk menentukan jumlah sampel peneliti menggunakan rumus slovin dengan taraf kesalahan 15% sehingga berdasarkan perhitungan mendapatkan 42 responden untuk wisatawan dan 44 responden untuk masyarakat desa. Teknik pengambilan data berupa kuesioner, observasi, dan dokumentasi.Penelitian ini menggunakan analisis SWOT dan analisis deskriptif. Hasil penelitian menunjukan dalam Matrix Grand Strategy terlihat hasil responden pengembangan berada di posisi kuadran 1 atau Strategi pertumbuhan, yaitu memanfaatkan seoptimal mungkin kekuatan dan peluang yang dimiliki. Kontribusi Obyek Wisata Curug bayan terhadap pemerintah desa sebesar 2% setiap tahunnya.